Evaluation of Drug Procurement Pattern and Drug Availability for JKN Patients at X Hospital and Y Hospital, Cirebon District, January-December 2022 Period - Siti Jabal Mastura; Prih Sarnianto; Shirly Kumala; Dosi Ahmad Yani; Hery Prambudi (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The era of National Health Insurance (JKN) brought changes in the health care system, which required hospital pharmacists to adapt to drug regulations and planning. Procurement planning and procedures have a significant impact on the availability of drugs and the financial situation of the hospital in drug management. One of the most crucial aspects of the hospital is the availability of guaranteed goods and sufficient drug supplies in order to provide the best service. This research was conducted to evaluate the procurement and availability of drugs at X Hospital as a public hospital and Y Hospital as a private hospital in Cirebon Regency. The analysis used in this study is descriptive-evaluative, namely the research method used to obtain data in a descriptive form and a systematic analysis is carried out to evaluate based on the descriptive data. Data collection was carried out by means of in-depth interviews with the hospital and distributors as external parties who also contributed to fulfilling the availability of drugs. The data is also complemented by the results of field observations and review of document reports related to the National Formulary (Fornas), Hospital Formulus (Forkit), and Drug Needs Plan (RKO). The results of this study found that the Drug Needs Plan, procurement and availability of drugs at X Hospital and Y Hospital were in accordance with the standards. This shows that most of the drugs available and given to patients are in accordance with the drugs listed in the National Formulary. There is a difference in the pattern of procurement. Hospitals conduct procurement twice a month, but private hospitals conduct procurement patterns twice a week. The two hospitals both use the SIMRS and Teramedik management information systems for the evaluation process of drug procurement and availability